The Emergence and Development of Women's Sports in Oman - Al Droushi, Abdul Rahim Muslem; Al Shukaili, Samira Shinain (Dirasat: Educational Sciences, 2021)
This study aims to investigate the emergence and development of women’s sports in Oman since the beginning of the Oman Renaissance era in 1970. The study is carried out through a qualitative design that implements a biographical approach. It explores the work history of eight interviewees from Omani sports sector and utilizes semi-structured interviews as well as document analysis as data collection methods. The data analysis method is Critical Discourse Analysis (CDA). The results show that women’s sports in Oman have emerged since the 1970s thanks to the physical education curriculum in Oman that helped spread modern sports among girls in the early decades of the Omani Renaissance. CDA shows that different factors influenced the development path of women’s sports in Oman, particularly norms and traditions, Islam and state policy. The study concludes that the development of women’s sports in Oman does not follow a distinct model that borrow other international experiences; instead, it manifests itself as a unique path of progress. In other words, it preserves the cultural and societal aspects through allowing restricted rules and procedures for women’s sports at the community level while allowing flexibility in participating at competitive level especially when it comes to competing at the international sphere.